Metabolic recovery from exhaustive activity by a large lizard. - Gleeson, T. T. (1980)
BIB Now: 3165
English
Keywords: PH, MI -- Metabolic recovery from exhaustive activity by a large lizard. -- Marine iguana, Amblyrhynchus cristatus, activity, physiology -- Iguana marina, Amblyrhynchus cristatus, actividad, fisiología